Coups and nascent democracies: the military and Egypt's failed consolidation. Issue 1 (2nd January 2017) - Bou Nassif, Hicham
ABSTRACT: Why do coups happen in some nascent democracies but not in others? To answer this question, I probe four interconnected variables in democratizing regimes: the military's ethos; the military's corporate interests; the military's perception of the new civilian ruling elite; and the correlation of force between the military and the founding democratic government. My argument is twofold: first, I maintain that ideational variables are central to shaping the military's political behaviour; and second, I argue in favour of merging insights from cultural, corporate, and structural theories to understand the consolidation, or breakdown, of nascent democracies.